2021
DOI: 10.1111/xen.12708
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human CD47 in pig glomeruli prevents proteinuria and prolongs graft survival following pig‐to‐baboon xenotransplantation

Abstract: Background Nephrotic syndrome is a common complication of pig‐to‐baboon kidney xenotransplantation (KXTx) that adversely affects outcomes. We have reported that upregulation of CD80 and down‐regulation of SMPDL‐3b in glomeruli have an important role in the development of proteinuria following pig‐to‐baboon KXTx. Recently we found induced expression of human CD47 (hCD47) on endothelial cells and podocytes isolated from hCD47 transgenic (Tg) swine markedly reduced phagocytosis by baboon and human macrophages. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…On a more granular level, studies have shown that human CD47 expression in pig endothelial cells and podocytes prevented phagocytosis by correcting CD47-SIRPα species incompatibilities and enabling normal SIRPα signal transduction. Indeed, hCD47 expression on podocytes in hCD47/GalTKO pig-to-baboon kidney transplants was shown to inhibit the development of proteinuria ( 59 ).. However, our data also demonstrated that high hCD47 expression in renal tubular cells may lead to destructive inflammatory responses via the hCD47-TSP-1 pathway ( 59 ).…”
Section: Genetic Engineering For Pig-to-primate Transplantationmentioning
confidence: 65%
See 3 more Smart Citations
“…On a more granular level, studies have shown that human CD47 expression in pig endothelial cells and podocytes prevented phagocytosis by correcting CD47-SIRPα species incompatibilities and enabling normal SIRPα signal transduction. Indeed, hCD47 expression on podocytes in hCD47/GalTKO pig-to-baboon kidney transplants was shown to inhibit the development of proteinuria ( 59 ).. However, our data also demonstrated that high hCD47 expression in renal tubular cells may lead to destructive inflammatory responses via the hCD47-TSP-1 pathway ( 59 ).…”
Section: Genetic Engineering For Pig-to-primate Transplantationmentioning
confidence: 65%
“…Indeed, hCD47 expression on podocytes in hCD47/GalTKO pig-to-baboon kidney transplants was shown to inhibit the development of proteinuria ( 59 ).. However, our data also demonstrated that high hCD47 expression in renal tubular cells may lead to destructive inflammatory responses via the hCD47-TSP-1 pathway ( 59 ). More research is needed to further refine and reliably predict gene expression in multiply modified pigs.…”
Section: Genetic Engineering For Pig-to-primate Transplantationmentioning
confidence: 65%
See 2 more Smart Citations
“…This approach has been investigated in the treatment of asthma, showing reduced allergic airway inflammation ( 49 ). Human CD47 transgenic pigs have been generated, and prolonged survival of human CD47 pig-derived xenografts in NHP has been achieved by reducing macrophage activation ( 46 , 50 , 51 ). Generating pigs with human leukocyte antigens-E (HLA-E) ( 52 ) or human leukocyte antigens-G (HLA-G) ( 53 ) has also been proposed as an additional option to inhibit human macrophage-mediated porcine islet xenograft rejection.…”
Section: Macrophage-mediated Cellular Immunoresponse In Islet Xenotra...mentioning
confidence: 99%